18. EVALUATION OF THE EFFECT OF THE MEDICINE THAN THONG TRUC U THANG FORMULA COMBINED WITH ELECTROACUPUNCTURE AND ACUPRESSURE MASSAGE ON PATIENTS WITH SCIATICA DUE TO LUMBAR DISC HERNIATION (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of the traditional herbal formula Than thong truc u thang combined with electroacupuncture and acupressure massage in patients with sciatica due to lumbar disc herniation.Method: A pre-post clinical intervention study was conducted on 30 patients diagnosed with sciatica due to lumbar disc herniation at Thai Binh Traditional Medicine Hospital.Results: After 14 days of treatment, the mean VAS score decreased from 6.43 ± 1.45 to 1.03 ± 0.76; the Lasègue sign increased from 55.50o ± 7.67o to 75.37o ± 7.63o. Lumbar spine range of motion significantly improved. The rate of patients with good outcomes was 33.33%, fair 56.67%, and average 10%. No patients had poor treatment outcomes.Conclusion: The herbal formula Than thong truc u thang combined with electroacupuncture and acupressure massage effectively reduces pain in treating sciatica caused by lumbar disc herniation.
Keywords: Sciatica; lumbar disc herniation; acupressure massage, electroacupuncture; Than thong truc u thang